Leseprojekte in der Sekundarstufe. Lesekompetenz, Lesemotivation, Lesedidaktik. - Gessner, Elisabeth (Kassel University Press, 2010)
In this book several selected projects developed by students of the University of Kassel on "Reading in the secondary school" ("Lesen in der Sekundarstufe") are presented. All projects concern the question of how to introduce children and young people with creativity and imagination in reading and how to improve their reading skills. The projects demonstrate a wide range of possible approaches, that differ in their didactic approaches and the individually chosen presentation.